How precisely can psychotherapists predict the long‐term outcome of anorexia nervosa and bulimia nervosa at the end of inpatient treatment?. Issue 4 (15th December 2020) - Fichter, Manfred M.; Quadflieg, Norbert
Abstract: Objective: To assess the ability of psychotherapists to predict the future outcome for inpatients with anorexia nervosa (AN) and bulimia nervosa (BN). Method: Psychotherapists rated the prognosis of the patient's eating disorder on a five point Likert scale on several dimensions at the end of inpatient treatment. Actual outcome was assessed about 10 years after treatment. The sample comprised 1, 065 patients treated for AN, and 1, 192 patients treated for BN. Results: Psychotherapists' rating of their patient's prognosis was not better than chance for good outcome in AN and BN and for poor outcome in BN. Prediction of poor outcome in AN was somewhat better with approximately two thirds of correct predictions. In logistic regression analysis, psychotherapists' rating of the patients' prognosis for AN contributed to the explained variance of long‐term outcome, increasing the variance explained from 7% (by conventional predictors) to 8% after including psychotherapists' prognosis. In BN, there was no significant contribution of psychotherapists' prognosis to overall prediction. Discussion: Our current knowledge of risk and protective factors for the course of eating disorders is unsatisfying. More specialized research is urgently needed.